Multi-component bicrystal hard alloy and preparation method thereof

By adopting the structural design of multi-component dual-crystal carbide, the combination of multi-component carbide hard phase and bonded phase in entropy alloy is solved, and the existing WC-Co carbide hard phase is difficult to have high hardness and high toughness at the same time is achieved, and a high-performance cemented carbide is achieved.

CN119710418APending Publication Date: 2025-03-28SEED TECH CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411968459.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing WC-Co carbide is difficult to have high hardness and high toughness at the same time, and the preparation method of particle size gradient alloy is complex, costly and expensive.

Method used

Multi-component dual-crystal carbide is used, consisting of multi-component carbide hard phase and bonded phase mid-entropy alloy. It forms excellent wetting through interface reaction, achieving coexistence of two grain structures of coarse and fine grain.

Benefits of technology

It realizes the high hardness, bending strength and fracture toughness of cemented carbide, and is suitable for high load and large impact fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005218936260000011
    Figure HDA0005218936260000011
Patent Text Reader

Abstract

The invention provides a multi-component bicrystal hard alloy. The multi-component bicrystal hard alloy is composed of a multi-component carbide hard phase and a binding phase medium entropy alloy, the multi-component carbide hard phase is composed of W, Mo, Cr and Ta or W, Mo, Cr and V; the entropy alloy in the binding phase is composed of three components of Co, Ni and Cu, three components of Co, Fe and Cu or four components of Co, Ni, Fe and Cu. The invention further provides a preparation method of the multi-component bicrystal hard alloy. According to the multi-component bicrystal hard alloy provided by the invention, through interface reaction among multi-component carbide hard phases and formation of excellent wettability with entropy alloy in a bonding phase, the multi-component bicrystal hard alloy can simultaneously have a coarse grain structure and a fine grain structure in a microstructure, the coarse grains can keep very high toughness, the fine grains have relatively high hardness and strength, and the multi-component bicrystal hard alloy can be used as a hard alloy material. The hard alloy with wear resistance and impact resistance is particularly suitable for being used in the fields of mine drilling, metal forming and the like which need to bear high load and large impact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cemented carbide, and in particular to a multi-component twin-crystal cemented carbide and a preparation method thereof. Background Art

[0002] Wear resistance and toughness are a mutually exclusive trade-off in cemented carbide. In recent years, a variety of new cemented carbides have been developed both domestically and internationally to achieve both high wear resistance and toughness, thereby improving the overall mechanical properties of mining cemented carbide, extending tool life, and reducing production costs. These new cemented carbides primarily include ultrafine and nano-grained cemented carbides, new binder phase structure cemented carbides, dual-grain structure cemented carbides, high-temperature powder-based cemented carbides, functionally graded structure cemented carbides, and low-cobalt coarse-grained cemented carbides.

[0003] Among various materials, hardness and toughness often trade off, and this is also true for WC-Co cemented carbide, making it difficult to achieve both high hardness and high toughness. Gradient alloys are considered an extremely important means of addressing these performance requirements. By adjusting the microstructure of the surface and core, different functional layers can be obtained, allowing them to be applied to different service conditions.

[0004] Grain-graded WC-Co cemented carbide refers to a cemented carbide in which the average WC grain size exhibits a gradient change from the surface to the core, either throughout the entire sample or in part. Currently, the primary method for preparing grain-graded WC-Co cemented carbide is layered pressing, where mixed WC-Co powders of varying average WC grain sizes are pressed through multiple stages to produce green compacts with varying grain size layers. While this layered pressing method can produce grain-graded alloys, it presents numerous other challenges. The pressing process is extremely complex and only suitable for green compacts with simple shapes; the grain size gradient exists only in the direction of pressure; and the requirement for multiple WC powders with varying average grain sizes leads to high production costs and difficult control processes, resulting in a costly product.

[0005] Therefore, it is of great significance to provide a cemented carbide with structural changes and high hardness and toughness. Summary of the Invention

[0006] The technical problem solved by the present invention is to provide a multi-component twin-crystal cemented carbide. The multi-component twin-crystal cemented carbide provided in this application has both high hardness and high toughness, and has both coarse and fine grain structures.

[0007] In view of this, the present application provides a multi-component twinned cemented carbide, which is composed of a multi-component carbide hard phase and a binder phase medium entropy alloy;

[0008] The multi-component carbide hard phase consists of W, Mo, Cr, Ta or W, Mo, Cr, V;

[0009] The entropy alloy in the bonding phase consists of three components of Co, Ni, and Cu, three components of Co, Fe, and Cu, or four components of Co, Ni, Fe, and Cu.

[0010] Preferably, in terms of atomic percentage, the multi-component carbide hard phase includes: C 37% to 61%, W 22% to 39%, Mo 3% to 11%, Cr 2% to 9%, Ta 0% to 9%, and V 0% to 9%, wherein Ta and V are not both 0% and are not included at the same time.

[0011] Preferably, in terms of atomic percentage, the entropy alloy in the binder phase consists of Co 10% to 13%, Ni 0.3% to 3%, and Cu 0.5% to 5%, or consists of Co 10% to 13%, Fe 0.5% to 5%, and Cu 0.5% to 5%, or consists of Co 10% to 13%, Ni 0.3% to 3%, Fe 0.5% to 5%, and Cu 0.5% to 5%.

[0012] Preferably, the cemented carbide comprises the following combination in atomic percentage:

[0013] Composed of C 37% to 61%, W 22% to 39%, Mo 3% to 11%, Cr 2% to 9%, Ta 0% to 9%, Co 10% to 13%, Ni 0.3% to 3%, Cu 0.5 to 5%, and Ta is not equal to 0%;

[0014] Or, composed of C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, V 0%-9%, Co 10%-13%, Ni 0.3%-3%, Cu 0.5-5%, and V is not equal to 0%;

[0015] Or, composed of C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, Ta 0%-9%, Co 10%-13%, Fe 0.5-5%, Cu 0.5-5%, and Ta is not equal to 0%;

[0016] Or, C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, V 0%-9%, Co 10%-13%, Fe 0.5-5%, Cu 0.5-5%, and V is not equal to 0%;

[0017] Or C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, Ta 0%-9%, Co 10%-13%, Ni 0.3%-3%, Fe 0.5-5%, Cu 0.5-5%, and Ta is not equal to 0%;

[0018] Or C 37%~61%, W 22%~39%, Mo 3%~11%, Cr 2%~9%, V 0%~9%, Co10%~13%, Ni 0.3%~3%, Fe 0.5~5%, Cu 0.5~5%, and V is not equal to 0%.

[0019] Preferably, the WC in the cemented carbide includes WC coarse grains and WC fine grains.

[0020] The present application also provides a method for preparing the multi-component twinned cemented carbide, comprising the following steps:

[0021] According to the composition of the multi-component carbide hard phase, multi-component carbide powder is used as the hard phase raw material;

[0022] Selecting medium entropy alloy raw material powder according to the composition of the medium entropy alloy in the binder phase;

[0023] The multi-component carbide powder and the medium entropy alloy raw material powder are mixed, sintered, and then heat treated to obtain a multi-component twinned cemented carbide.

[0024] Preferably, the sintering is gas pressure sintering, the sintering temperature is 1000-1500°C, the time is 500-1000 min, the sintering pressure is 5-10 MPa, and the sintering is carried out under vacuum, hydrogen and argon protection conditions;

[0025] Alternatively, the sintering is spark plasma sintering, the sintering temperature is 1200-1600° C., the time is 10-100 min, the sintering pressure is 15-30 MPa, and the sintering is performed under vacuum.

[0026] Preferably, the heat treatment temperature is 500-1000° C., and the time is 300-600 min; and the heat treatment is performed under vacuum conditions.

[0027] Preferably, the mixing method is wet ball milling, the ball-to-material ratio of the wet ball milling is (5-10):1, the ball mill speed is 100-500 rpm, the time is 20-80 h, and the wet ball milling further includes drying at 80-150° C. for 3-10 h and then sieving;

[0028] Alternatively, the mixing method is dry grinding under argon conditions, the ball-to-material ratio of the dry grinding is (5-10):1, the ball mill speed is 100-500 rpm, the time is 10-20 h, and the dry grinding also includes screening under argon protection.

[0029] Preferably, the mixing further includes pre-milling of the multi-component carbide powder:

[0030] The multi-component carbide powder is dry-milled under argon protection, with a ball-to-material ratio of (5-10):1, a ball mill speed of 100-500 revolutions, and a grinding time of 10-20 hours. After the dry-milling, the powder is sieved under argon protection.

[0031] The present application provides a multi-component bi-crystal cemented carbide, which is composed of a multi-component carbide hard phase and an entropy alloy in a binder phase, wherein the multi-component carbide hard phase is composed of W, Mo, Cr, Ta or W, Mo, Cr, and V; and the entropy alloy in the binder phase is composed of a three-component composition of Co, Ni, and Cu, a three-component composition of Co, Fe, and Cu, or a four-component composition of Co, Ni, Fe, and Cu. The multi-component bi-crystal cemented carbide provided in the present application has excellent wettability with the entropy alloy in the binder phase through interfacial reactions between the multi-component hard phases, thereby achieving both coarse and fine grain structures in the microstructure, thereby ensuring the hardness and toughness of the cemented carbide. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a metallographic photograph of the multi-component twin-crystal cemented carbide prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0034] In view of the problem that cemented carbide in the prior art cannot have both wear resistance and toughness, the present application provides a multi-component twin-crystal cemented carbide, which is composed of a multi-component carbide hard phase and an entropy alloy in a binder phase. By adjusting the composition of the multi-component carbide hard phase and the entropy alloy in the binder phase, the obtained multi-component twin-crystal cemented carbide has two coarse and fine grain structures, and ultimately the cemented carbide has both wear resistance and toughness. Specifically, an embodiment of the present invention discloses a multi-component twin-crystal cemented carbide, which is composed of a multi-component carbide hard phase and an entropy alloy in a binder phase;

[0035] The multi-component carbide hard phase consists of W, Mo, Cr, Ta or W, Mo, Cr, V;

[0036] The entropy alloy in the bonding phase consists of three components of Co, Ni, and Cu, three components of Co, Fe, and Cu, or four components of Co, Ni, Fe, and Cu.

[0037] In the multi-component twin-crystal cemented carbide provided in the present application, the hard phase in the multi-component carbide hard phase is composed of W, Mo, Cr, Ta, or composed of W, Mo, Cr, V, and further contains C, and the above-mentioned hard phase forms carbide with C as a hard phase; further, the multi-component carbide hard phase includes: C 37% to 61%, W 22% to 39%, Mo 3% to 11%, Cr 2% to 9%, Ta 0% to 9%, V 0% to 9%, Ta and V are not 0% at the same time and are not included at the same time; specifically, the multi-component carbide hard phase includes C 37% to 61%, W 22% to 39%, Mo 3% to 11%, Cr 2% to 9%, Ta 0% to 9%, wherein Ta is not 0%, more specifically, C 39% to 50%, W 25% to 30%, Mo 4% to 10%, Cr %~8%, Ta2%~7%, more specifically, C 42%~48%, W 26%~28%, Mo 5%~7%, Cr5%~7%, Ta 3%~5%; or, C 37%~61%, W 22%~39%, Mo 3%~11%, Cr 2%~9%, V 0%~9%, wherein V is not 0%, more specifically, C 39%~50%, W 25%~30%, Mo 4%~10%, Cr4%~8%, V 2%~7%, more specifically, C 42%~48%, W 26%~28%, Mo 5%~7%, Cr 5%~7%, V 3%~5%.

[0038] The entropy alloy in the binder phase consists of Co 10% to 13%, Ni 0.3% to 3%, and Cu 0.5% to 5%, specifically, Co 11% to 12.5%, Ni 0.5% to 2%, and Cu 0.5% to 4%, more specifically, Co 11.5% to 12%, Ni 1% to 1.5%, and Cu 1% to 3%;

[0039] Or composed of Co 10%-13%, Fe 0.5%-5%, Cu 0.5%-5%, specifically, composed of Co 11%-12.5%, Fe 1%-4%, Cu 0.5-4%, more specifically, composed of Co 11.5%-12%, Fe 1.5%-3%, Cu 1-3%;

[0040] Or it is composed of Co 10%-13%, Ni 0.3%-3%, Fe 0.5-5%, and Cu 0.5-5%, specifically, it is composed of Co 11%-12.5%, Ni 0.5%-2%, Fe 1%-4%, and Cu 0.5-4%, more specifically, it is composed of Co 11.5%-12%, Ni 1%-1.5%, Fe 1.5%-3%, and Cu 1-3%.

[0041] The atomic percentages of Co, Ni and / or Fe, Cu, W, Mo, Cr, Ta / V, and C mentioned above are based on the total elements in the cemented carbide.

[0042] Furthermore, the cemented carbide described in this application includes the following combinations:

[0043] Composed of C 37% to 61%, W 22% to 39%, Mo 3% to 11%, Cr 2% to 9%, Ta 0% to 9%, Co 10% to 13%, Ni 0.3% to 3%, Cu 0.5 to 5%, and Ta is not equal to 0%;

[0044] Or, composed of C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, V 0%-9%, Co 10%-13%, Ni 0.3%-3%, Cu 0.5-5%, and V is not equal to 0%;

[0045] Or, composed of C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, Ta 0%-9%, Co 10%-13%, Fe 0.5-5%, Cu 0.5-5%, and Ta is not equal to 0%;

[0046] Or, C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, V 0%-9%, Co 10%-13%, Fe 0.5-5%, Cu 0.5-5%, and V is not equal to 0%;

[0047] Or C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, Ta 0%-9%, Co 10%-13%, Ni 0.3%-3%, Fe 0.5-5%, Cu 0.5-5%, and Ta is not equal to 0%;

[0048] Or C 37%~61%, W 22%~39%, Mo 3%~11%, Cr 2%~9%, V 0%~9%, Co10%~13%, Ni 0.3%~3%, Fe 0.5~5%, Cu 0.5~5%, and V is not equal to 0%.

[0049] In the case of the above combination, the preferred scheme of the elements is selected according to the above preferred range, which will not be described in detail in this application.

[0050] Furthermore, the WC in the cemented carbide of the present application includes WC coarse grains and WC fine grains.

[0051] The present application also provides a method for preparing a multi-component twinned cemented carbide, comprising the following steps:

[0052] According to the composition of the multi-component carbide hard phase, multi-component carbide powder is used as the hard phase raw material;

[0053] Selecting medium entropy alloy raw material powder according to the composition of the medium entropy alloy in the binder phase;

[0054] The multi-component carbide powder and the medium entropy alloy raw material powder are mixed, sintered, and then heat treated to obtain a multi-component twinned cemented carbide.

[0055] In the preparation method of multi-component twinned cemented carbide, the present application first uses multi-component carbide powder as the hard phase raw material according to the composition of the multi-component carbide hard phase; for example, to prepare a multi-component carbide hard phase (WMoCrTa)C, WC, Mo2C, Cr3C2, TaC, and W can be selected as raw materials; that is, the selection of the hard phase raw material can be made according to the composition of the multi-component carbide hard phase according to the choice of those skilled in the art, but it is necessary to meet the ratio of the multi-component carbide hard phase. After the raw material ratio is completed, the present application preferably pre-mills the multi-component carbide powder, specifically:

[0056] The multi-component carbide powder is dry-milled under argon protection, with a ball-to-material ratio of (5-10):1, a ball mill speed of 100-500 revolutions, and a grinding time of 10-20 hours. After the dry-milling, the powder is sieved under argon protection.

[0057] During the above-mentioned pre-ball milling process, the ball-to-material ratio of the dry milling is (5-8):1, the ball mill speed is 100-400 rpm, and the time is 12-18 hours.

[0058] After the above-mentioned pre-ball milling, coarse-grained multi-component carbide powder and fine-grained multi-component carbide powder are obtained, and the fine-grained multi-component carbide powder is further mixed with the medium-entropy alloy raw material powder.

[0059] Furthermore, the medium entropy alloy raw material powder is selected according to the composition of the medium entropy alloy in the binder phase.

[0060] The present application then mixes the multi-component carbide powder and the medium entropy alloy raw material powder, sintering them, and then heat treating them to obtain a multi-component twinned cemented carbide. In this process, the mixing preferably first mixes the above-mentioned fine-grained multi-component carbide powder and the medium entropy alloy raw material powder and then mixes them with the coarse-grained multi-component carbide powder to obtain a mixture; the first mixing can be wet ball milling or dry milling; the ball-to-material ratio of the wet ball milling is (5-10):1, the ball mill speed is 100-500 rpm, and the time is 20-80h. After the wet ball milling, it also includes drying at 80-150°C for 3-10h and then sieving; specifically, the ball-to-material ratio of the wet ball milling is (5-8):1, the ball mill speed is 100-400 rpm, and the time is 30-60h. After the wet ball milling, it also includes drying at 80-120°C for 3-8h and then sieving. The dry milling is preferably carried out under argon conditions, with a ball-to-material ratio of (5-10):1, a ball mill speed of 100-500 rpm, and a time of 10-20 hours. The dry milling also includes screening under argon protection. Specifically, the dry milling has a ball-to-material ratio of (5-8):1, a ball mill speed of 100-400 rpm, and a time of 12-18 hours. The powder obtained after the above mixing is then mixed with the above coarse-grained multi-component carbide to obtain a mixed material.

[0061] The present application then uses cold pressing to form the above-mentioned mixture into a powder blank, and then sintering it. The sintering is gas pressure sintering, the sintering temperature is 1000-1500℃, the time is 500-1000min, the sintering pressure is 5-10MPa, and the sintering is carried out under vacuum, hydrogen and argon protection conditions; specifically, the sintering temperature is 1350-1450℃, the time is 600-700min, and the sintering pressure is 7-9MPa. Alternatively, the sintering is spark plasma sintering, the sintering temperature is 1200-1600℃, the time is 10-100min, the sintering pressure is 15-30MPa, and the sintering is carried out under vacuum; specifically, the sintering temperature is 1300-1400℃, the time is 30-60min, and the sintering pressure is 20-25MPa. The sintering achieves the forming of a high-strength and high-hardness blank.

[0062] According to the present invention, the sintered material is finally subjected to heat treatment at a temperature of 500-1000°C and a time of 300-600 minutes; the heat treatment is carried out under vacuum conditions; specifically, the heat treatment temperature is 650-750°C and a time of 450-550 minutes.

[0063] The present invention provides a multi-component twinned cemented carbide, which uses multi-component carbides as the hard phase and Co, Ni, Fe, and Cu as the entropy alloy components in the binder phase. Through the interfacial reaction between the multi-component hard phases and the formation of excellent wettability with the entropy alloy in the binder phase, the microstructure can have both coarse and fine grain structures. The Rockwell hardness of this cemented carbide is 85-90 HRA and the bending strength is 4000-4500 N / mm 2 , fracture toughness (HV50) is 30~35MPa / m 2 , while having both hardness, strength and toughness, this high-performance cemented carbide can be used in fields such as mining drilling and metal forming that need to withstand high loads and large impacts.

[0064] In order to further understand the present invention, the multi-component twinned cemented carbide and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0065] Unless otherwise specified, the raw materials used in the examples were purchased commercially.

[0066] Example 1

[0067] (1) According to the chemical formula (W 30 Mo 10 Cr5Ta5)C 37 The raw materials are metal carbide (WC, Mo2C, Cr3C2, TaC, W) powder with a particle size of 1-3 μm. The powder is placed in a ball mill filled with Ar gas and sealed. It is ball milled on a planetary ball mill for 80 hours with a ball-to-material ratio of 5:1 and a rotation speed of 300 revolutions per minute. The powder is then sieved under Ar gas protection to obtain a particle size of <200 mesh (W 30 Mo 10 Cr5Ta5)C 37 Multi-component carbide coarse powder and particle size ≥200 mesh (W 30 Mo 10 Cr5Ta5)C 37 Multi-component carbide fine powder;

[0068] (2) The particle size is less than 200 mesh (W 30 Mo 10 Cr5Ta5)C 37 Multi-component carbide fine powder and Co 11.5 Ni1Cu 0.5 The medium entropy alloy raw material powder was mixed, PEG (2wt%) and 75% alcohol were added, the ball-to-material ratio was 8:1, the rotation speed was 100 revolutions per minute, ball milling was carried out for 50 hours, and the powder was dried in a vacuum drying oven at 80℃ for 5 hours. The powder was sieved to obtain a cemented carbide powder with uniform particle size, and then mixed with a particle size of ≥200 mesh (W30 Mo 10 Cr5Ta5)C 37 Multi-component carbide coarse powder is mixed and cold pressed into test bars, which are then placed in a pressure sintering furnace for gas pressure sintering at a sintering temperature of 1430±10°C and a sintering pressure of 8±1 MPa. After sintering, a dense block material is obtained, which is then annealed in a vacuum furnace at a temperature of 700±50°C and a time of 500±50 minutes. The annealing process is carried out under vacuum conditions.

[0069] Figure 1 This is a metallographic structure photograph of the cemented carbide prepared in this embodiment. It can be clearly seen from the figure that the cemented carbide prepared in this embodiment includes a coarse-fine grain structure of coarse grains and fine grains.

[0070] The sample block of the high-strength and high-toughness multi-component twin-crystal cemented carbide obtained in Example 1 was flat-ground to obtain a standard B406 test block. The hardness (HRA) was tested using a HES-150 digital Rockwell hardness tester (China) (GB3849), the flexural strength (TRS) was tested using a WE-100 100KN hydraulic universal testing machine (China) (GB3851, B sample), and the fracture toughness was tested using a Vickers hardness tester VH1150 (GB4161, HV50) indentation method. After the test, the test block had a Rockwell hardness of 90HRA and a flexural strength of 4300N / mm 2 , fracture toughness (HV50) is 31MPa / m 2 .

[0071] Example 2

[0072] (1) According to the chemical formula (W 30 Mo 10 Cr5Ta5)C 37 The raw materials are metal carbide (WC, Mo2C, Cr3C2, TaC, W) powder with a particle size of 1-3 μm. The powder is placed in a ball mill filled with Ar gas and sealed. It is ball milled on a planetary ball mill for 80 hours with a ball-to-material ratio of 5:1 and a rotation speed of 300 revolutions per minute. The powder is then sieved under Ar gas protection to obtain a particle size of <200 mesh (W 30 Mo 10 Cr5Ta5)C 37 Multi-component carbide powder and particle size ≥ 200 mesh (W 30 Mo 10 Cr5Ta5)C 37 Multi-component carbide powder;

[0073] (2) The particle size is less than 200 mesh (W 30 Mo 10 Cr5Ta5)C 37Multi-component carbide powder and Co 11.5 Fe1Cu 0.5 The medium entropy alloy raw material powder was batched, PEG (2wt%) and 75% alcohol were added, the ball-to-material ratio was 8:1, the rotation speed was 100 revolutions per minute, ball milling was carried out for 50 hours, and the powder was dried in a vacuum drying oven at 80℃ for 5 hours. The powder was sieved to obtain a cemented carbide powder with uniform particle size, and then mixed with a particle size ≥80 mesh (W 30 Mo 10 Cr5Ta5)C 37 After mixing, multi-component carbide powders are cold-pressed into test bars, which are then placed in a pressure sintering furnace for gas pressure sintering at a sintering temperature of 1430±10°C and a sintering pressure of 8±1 MPa. After sintering, a dense block material is obtained, which is then annealed in a vacuum furnace at a temperature of 700±50°C and a time of 500±50 minutes. The annealing process is carried out under vacuum conditions.

[0074] The high-strength and high-toughness multi-component twin-crystal carbide sample block obtained in Example 2 was flat-ground to obtain a standard B406 test block. The hardness (HRA) was tested using a HES-150 digital Rockwell hardness tester (China) (GB3849), the flexural strength (TRS) was tested using a WE-100 100KN hydraulic universal testing machine (China) (GB3851, B specimen), and the fracture toughness was tested using a Vickers hardness tester VH1150 (GB4161, HV50) indentation method. After the test, the test block had a Rockwell hardness of 88HRA and a flexural strength of 4100N / mm 2 , fracture toughness (HV50) is 30MPa / m 2 .

[0075] Example 3

[0076] (1) According to the chemical formula (W 30 Mo 10 Cr5Ta5)C 37 The raw materials are metal carbide (WC, Mo2C, Cr3C2, TaC, W) powder with a particle size of 1-3 μm. The powder is placed in a ball mill filled with Ar gas and sealed. It is ball milled on a planetary ball mill for 80 hours with a ball-to-material ratio of 5:1 and a rotation speed of 300 revolutions per minute. The powder is then sieved under Ar gas protection to obtain a particle size of <200 mesh (W 30 Mo 10 Cr5Ta5)C 37 Multi-component carbide powder and particle size ≥ 200 mesh (W 30 Mo 10 Cr5Ta5)C 37 Multi-component carbide powder;

[0077] (2) The particle size is less than 200 mesh (W30 Mo 10 Cr5Ta5)C 37 Multi-component carbide powder and Co 11.5 Ni 0.5 Fe 0.5 Cu 0.5 The medium entropy alloy raw material powder was batched, PEG (2wt%) and 75% alcohol were added, the ball-to-material ratio was 8:1, the rotation speed was 100 revolutions per minute, ball milling was carried out for 50 hours, and the powder was dried in a vacuum drying oven at 80℃ for 5 hours. The powder was sieved to obtain a cemented carbide powder with uniform particle size, and then mixed with a particle size ≥80 mesh (W 30 Mo 10 Cr5Ta5)C 37 After mixing, multi-component carbide powders are cold-pressed into test bars, which are then placed in a pressure sintering furnace for gas pressure sintering at a sintering temperature of 1430±10°C and a sintering pressure of 8±1 MPa. After sintering, a dense block material is obtained, which is then annealed in a vacuum furnace at a temperature of 700±50°C and a time of 500±50 minutes. The annealing process is carried out under vacuum conditions.

[0078] The high-strength and high-toughness multi-component twin-crystal carbide sample block obtained in Example 3 was flat-ground to obtain a standard B406 test block. The hardness (HRA) was tested using a HES-150 digital Rockwell hardness tester (China) (GB3849), the flexural strength (TRS) was tested using a WE-100 100KN hydraulic universal testing machine (China) (GB3851, B specimen), and the fracture toughness was tested using a Vickers hardness tester VH1150 (GB4161, HV50) indentation method. After the test, the test block had a Rockwell hardness of 89HRA and a flexural strength of 4200N / mm 2 , fracture toughness (HV50) is 33MPa / m 2 .

[0079] Example 4

[0080] (1) According to the chemical formula (W 30 Mo 10 Cr5V5)C 37 The raw materials are metal carbide (WC, Mo2C, Cr3C2, VC, W) powder with a particle size of 1-3 μm. The powder is placed in a ball mill filled with Ar gas and sealed. It is ball milled on a planetary ball mill for 80 hours with a ball-to-material ratio of 5:1 and a rotation speed of 300 revolutions per minute. The powder is then sieved under Ar gas protection to obtain a particle size of <200 mesh (W 30 Mo 10 Cr5V5)C 37 Multi-component carbide powder and particle size ≥ 200 mesh (W 30 Mo 10Cr5V5)C 37 Multi-component carbide powder;

[0081] (2) The particle size is less than 200 mesh (W 30 Mo 10 Cr5V5)C 37 Multi-component carbide powder and Co 11.5 Ni1Cu 0.5 The medium entropy alloy raw material powder was mixed, PEG (2wt%) and 75% alcohol were added, the ball-to-material ratio was 8:1, the rotation speed was 100 revolutions per minute, and the ball milling was carried out for 50 hours. The powder was dried in a vacuum drying oven at 80℃ for 5 hours, and the cemented carbide powder with uniform particle size was obtained by sieving the powder. The powder was then mixed with the particle size ≥200 mesh (W 30 Mo 10 Cr5V5)C 37 After mixing, multi-component carbide powders are cold-pressed into test bars, which are then placed in a pressure sintering furnace for gas pressure sintering at a sintering temperature of 1430±10°C and a sintering pressure of 8±1 MPa. After sintering, a dense block material is obtained, which is then annealed in a vacuum furnace at a temperature of 700±50°C and a time of 500±50 minutes. The annealing process is carried out under vacuum conditions.

[0082] The sample block of the high-strength and high-toughness multi-component twin-crystal cemented carbide obtained in Example 4 was flat-ground to obtain a standard B406 test block. The hardness (HRA) was tested using a HES-150 digital Rockwell hardness tester (China) (GB3849), the flexural strength (TRS) was tested using a WE-100 100KN hydraulic universal testing machine (China) (GB3851, B sample), and the fracture toughness was tested using a Vickers hardness tester VH1150 (GB4161, HV50) indentation method. After the test, the test block had a Rockwell hardness of 90HRA and a flexural strength of 4400N / mm 2 , fracture toughness (HV50) is 34MPa / m 2 .

[0083] Example 5

[0084] (1) According to the chemical formula (W 30 Mo 10 Cr5V5)C 37 The raw materials are metal carbide (WC, Mo2C, Cr3C2, VC, W) powder with a particle size of 1-3 μm. The powder is placed in a ball mill filled with Ar gas and sealed. It is ball milled on a planetary ball mill for 80 hours with a ball-to-material ratio of 5:1 and a rotation speed of 300 revolutions per minute. The powder is then sieved under Ar gas protection to obtain a particle size of <200 mesh (W 30 Mo 10 Cr5V5)C 37Multi-component carbide powder and particle size ≥ 200 mesh (W 30 Mo 10 Cr5V5)C 37 Multi-component carbide powder;

[0085] (2) The particle size is less than 200 mesh (W 30 Mo 10 Cr5V5)C 37 Multi-component carbide powder and Co 11.5 Fe1Cu 0.5 The medium entropy alloy raw material powder was mixed, PEG (2wt%) and 75% alcohol were added, the ball-to-material ratio was 8:1, the rotation speed was 100 revolutions per minute, and the ball milling was carried out for 50 hours. The powder was dried in a vacuum drying oven at 80℃ for 5 hours, and the cemented carbide powder with uniform particle size was obtained by sieving the powder. The powder was then mixed with the particle size ≥200 mesh (W 30 Mo 10 Cr5V5)C 37 After mixing, multi-component carbide powders are cold-pressed into test bars, which are then placed in a pressure sintering furnace for gas pressure sintering at a sintering temperature of 1430±10°C and a sintering pressure of 8±1 MPa. After sintering, a dense block material is obtained, which is then annealed in a vacuum furnace at a temperature of 700±50°C and a time of 500±50 minutes. The annealing process is carried out under vacuum conditions.

[0086] The sample block of the high-strength and high-toughness multi-component twin-crystal cemented carbide obtained in Example 5 was flat-ground to obtain a standard B406 test block. The hardness (HRA) was tested using a HES-150 digital Rockwell hardness tester (China) (GB3849), the flexural strength (TRS) was tested using a WE-100 100KN hydraulic universal testing machine (China) (GB3851, B sample), and the fracture toughness was tested using a Vickers hardness tester VH1150 (GB4161, HV50) indentation method. After the test, the test block had a Rockwell hardness of 88HRA and a flexural strength of 4000N / mm 2 , fracture toughness (HV50) is 31MPa / m 2 .

[0087] Example 6

[0088] (1) According to the chemical formula (W 30 Mo 10 Cr5V5)C 37 The raw materials are metal carbide (WC, Mo2C, Cr3C2, VC, W) powder with a particle size of 1-3 μm. The powder is placed in a ball mill filled with Ar gas and sealed. It is ball milled on a planetary ball mill for 80 hours with a ball-to-material ratio of 5:1 and a rotation speed of 300 revolutions per minute. The powder is then sieved under Ar gas protection to obtain a particle size of <200 mesh (W30 Mo 10 Cr5V5)C 37 Multi-component carbide powder and particle size ≥ 200 mesh (W 30 Mo 10 Cr5V5)C 37 Multi-component carbide powder;

[0089] (2) The particle size is less than 200 mesh (W 30 Mo 10 Cr5V5)C 37 Multi-component carbide powder and Co 11.5 Ni 0.5 Fe 0.5 Cu 0.5 The medium entropy alloy raw material powder was mixed, PEG (2wt%) and 75% alcohol were added, the ball-to-material ratio was 8:1, the rotation speed was 100 revolutions per minute, and the ball milling was carried out for 50 hours. The powder was dried in a vacuum drying oven at 80℃ for 5 hours, and the cemented carbide powder with uniform particle size was obtained by sieving the powder. The powder was then mixed with the particle size ≥200 mesh (W 30 Mo 10 Cr5V5)C 37 After mixing, multi-component carbide powders are cold-pressed into test bars, which are then placed in a pressure sintering furnace for gas pressure sintering at a sintering temperature of 1430±10°C and a sintering pressure of 8±1 MPa. After sintering, a dense block material is obtained, which is then annealed in a vacuum furnace at a temperature of 700±50°C and a time of 500±50 minutes. The annealing process is carried out under vacuum conditions.

[0090] The sample block of the high-strength and high-toughness multi-component twin-crystal cemented carbide obtained in Example 6 was flat-ground to obtain a standard B406 test block. The hardness (HRA) was tested using a HES-150 digital Rockwell hardness tester (China) (GB3849), the flexural strength (TRS) was tested using a WE-100 100KN hydraulic universal testing machine (China) (GB3851, B sample), and the fracture toughness was tested using a Vickers hardness tester VH1150 (GB4161, HV50) indentation method. After the test, the test block had a Rockwell hardness of 87HRA and a flexural strength of 4500N / mm 2 , fracture toughness (HV50) is 35MPa / m 2 .

[0091] The above embodiments are only intended to help understand the method and core concept of the present invention. It should be noted that, without departing from the principles of the present invention, a number of improvements and modifications may be made to the present invention by those skilled in the art, and such improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0092] The above description of the disclosed embodiments is intended to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is intended to conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A multi-component twinned cemented carbide, consisting of a multi-component carbide hard phase and a binder phase medium entropy alloy; The multi-component carbide hard phase consists of W, Mo, Cr, Ta or W, Mo, Cr, V; The entropy alloy in the bonding phase is composed of three components of Co, Ni and Cu, three components of Co, Fe and Cu, or four components of Co, Ni, Fe and Cu.

2. The multi-component twin-crystal cemented carbide according to claim 1, characterized in that: In terms of atomic percentage, the multi-component carbide hard phase includes: C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, Ta 0%-9%, V 0%-9%, Ta and V are not 0% at the same time and are not included at the same time.

3. The multi-component twinned cemented carbide according to claim 1, characterized in that: In terms of atomic percentage, the entropy alloy in the bonding phase consists of Co 10% to 13%, Ni 0.3% to 3%, and Cu 0.5% to 5% or consists of Co 10% to 13%, Fe 0.5% to 5%, and Cu 0.5% to 5% or consists of Co 10% to 13%, Ni 0.3% to 3%, Fe 0.5% to 5%, and Cu 0.5% to 5%.

4. The multi-component twinned cemented carbide according to claim 1, characterized in that: In terms of atomic percentage, the cemented carbide comprises the following combination: Composed of C 37% to 61%, W 22% to 39%, Mo 3% to 11%, Cr 2% to 9%, Ta 0% to 9%, Co 10% to 13%, Ni 0.3% to 3%, Cu 0.5 to 5%, and Ta is not equal to 0%; Or, composed of C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, V 0%-9%, Co10%-13%, Ni 0.3%-3%, Cu 0.5-5%, and V is not equal to 0%; Or, composed of C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, Ta 0%-9%, Co10%-13%, Fe 0.5-5%, Cu 0.5-5%, and Ta is not equal to 0%; Or, C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, V0%-9%, Co 10%-13%, Fe 0.5-5%, Cu 0.5-5%, and V is not equal to 0%; Or C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, Ta0%-9%, Co 10%-13%, Ni 0.3%-3%, Fe 0.5-5%, Cu 0.5-5%, and Ta is not equal to 0%; Or C 37%-61%, W 22%-39%, Mo 3%-11%, Cr 2%-9%, V 0%-9%, Co 10%-13%, Ni 0.3%-3%, Fe 0.5-5%, Cu 0.5-5%, and V is not equal to 0%.

5. The multi-component twinned cemented carbide according to claim 1, characterized in that: The WC in the cemented carbide includes WC coarse grains and WC fine grains.

6. The method for preparing the multi-component twinned cemented carbide according to any one of claims 1 to 5, comprising the following steps: According to the composition of the multi-component carbide hard phase, multi-component carbide powder is used as a hard phase raw material; Selecting medium entropy alloy raw material powder according to the composition of the medium entropy alloy in the binder phase; The multi-component carbide powder and the medium entropy alloy raw material powder are mixed, sintered, and then heat treated to obtain a multi-component twin-crystal cemented carbide.

7. The preparation method according to claim 6, characterized in that: The sintering is gas pressure sintering, the sintering temperature is 1000-1500°C, the time is 500-1000 min, the sintering pressure is 5-10 MPa, and the sintering is carried out under vacuum, hydrogen and argon protection conditions; or, the sintering is spark plasma sintering, the sintering temperature is 1200-1600°C, the time is 10-100 min, the sintering pressure is 15-30 MPa, and the sintering is carried out under vacuum.

8. The preparation method according to claim 6 or 7, characterized in that: The heat treatment is performed at a temperature of 500 to 1000° C. and for a time of 300 to 600 minutes; the heat treatment is performed under vacuum conditions.

9. The preparation method according to claim 6, characterized in that: The mixing method is wet ball milling, the ball-to-material ratio of the wet ball milling is (5-10):1, the ball mill speed is 100-500 revolutions, the time is 20-80 hours, and the wet ball milling also includes drying at 80-150° C. for 3-10 hours and then screening; Alternatively, the mixing method is dry grinding under argon conditions, the ball-to-material ratio of the dry grinding is (5-10):1, the ball mill speed is 100-500 rpm, the time is 10-20 hours, and the dry grinding also includes screening under argon protection.

10. The preparation method according to claim 6 or 9, characterized in that: The mixing also includes pre-milling of the multi-component carbide powder: The multi-component carbide powder is dry-milled under argon protection, the ball-to-material ratio of the dry-milling is (5-10):1, the ball mill speed is 100-500 revolutions, the time is 10-20 hours, and after the dry-milling, the powder is sieved under argon protection.